Body Fat, Body Fat Distribution, Lean Body Mass and Atrial Fibrillation and Flutter. A Danish Cohort Study - Frost, Lars (2014)
OBJECTIVE: It is recognized that higher height and weight are associated with higher risk of atrial fibrillation or flutter (AF) but it is unclear whether risk of AF is related to body fat, body fat location, or lean body mass. DESIGN AND METHODS: We studied the Danish population-based prospective cohort Diet, Cancer and Health conducted among 55 273 men and women 50-64 years of age at recruitment. We investigated the associations between bioelectrical impedance derived measures of body composition and combinations of anthropometric measures of body fat distribution and risk of an incident record of AF in the Danish Registry of Patients. RESULTS: During follow-up (median 13.5 years) AF developed in 1 669 men and 912 women. Higher body fat at any measured location was associated with higher risk of AF. The adjusted hazard ratio (HR) per 1 sex-specific standard deviation (SD) increment in body fat mass was 1.29 (95% confidence interval [CI], 1.24-1.33). Higher lean body mass was also associated with a higher risk of AF. The adjusted HR for 1 sex-specific SD increment was 1.40 (95% CI, 1.35-1.45). CONCLUSION: Higher body fat and higher lean body mass were both associated with higher risk of AF.